Pressing Rhythms and Korean Percussion Music - Cohn, Richard (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2025)
Jeff Pressing identified a group of seven jazz scale-classes that lack [0, 1, 2] subsets, but any added note would create a [0, 1, 2] subset. This article introduces Pressing rhythms in 12-beat cycles, which lack three consecutive onsets, but to which an added onset would create a three-onset run. The seven Pressing rhythm classes are prominent in p’ungmul, a genre of South Korean ensemble drumming that has been extensively researched by Nathan Hesselink. Juxtaposition of Pressing rhythms exploits the close parallelisms between them, with incremental one-onset changes akin to parsimonious voice leading between scales or chords.